Assessment of miR-146a Gene Polymorphisms in Patients with Systemic Lupus Erythematosus - Abdulridha, Ruaa Hameed; Saud, Asmaa Mohammed; Alosami, Mohammed Hadi (Iraqi Journal of Science, 2023)
Systemic lupus erythematosus (SLE) is a multifactorial chronic autoimmune disease, with a wide spectrum of effect. The main feature of the disease is the production of a wide variety of autoantibodies as a result of immune tolerance loss. The work aims to evaluate the miRNA-146a gene polymorphism potential association with disease activity and chronicity changes in SLE patients. The study included 100 SLE patients and 50 matched controls. The systemic lupus erythematosus disease activity index (SLEDAI) was assessed. The single nucleotide polymorphism (SNP) of miR-146a gene (rs2910164) polymorphism was assayed by polymerase chain reaction (PCR) and sequencing technique in patients and control. 100 SLE patients were all females and with a mean of age 31.3 ± 10 years (16-63years) and disease duration of 5.8 ± 3.7years (1 month to 15 years). Most clinical manifestations presented in patients were 52% malar rash, 45% oral ulcers, 54% arthritis, and 45% neurological disorder. Proteinuria, ESR, creatinine and AST were significantly higher (65% vs. 10%, 4.1±36.1 vs. 11.8±9.9 mm/hr, 0.62±0.11 vs. 0.70±0.14 mg/dl and 25.37±26.50 vs. 17.23±3.58 U/L respectively) while the PLT was significantly lower (231.9±88.8 vs. 282.3±67.3 103/mL) (p< 0.001) among SLE patients as compared to control. There were no significant variations in all study parameters across miRNA-146a genotypes (p greater than 0.05). There was a significant association of the homozygote GG genotype (66.7%) with the active SLE state (p=0.013). In conclusion, the results suggest a risk effect for the female gender and adult at a young age in the etiology of SLE. The miRNA-146a GG genotype is associated with increasing the disease activity and miRNA-146a polymorphism is not associated with the risk in SLE.